Age-dependent increase of collagenase expression can be reduced by alpha-tocopherol via protein kinase C inhibition - (:unkn) unknown (ELSEVIER SCIENCE INC, 1999)
Total protein kinase C (PKC) activity in human skin fibroblasts increases during in vivo aging as a function of the donor's age. During in vitro aging protein kinase C activity is also increased, as a function of cell passage number. Using PKC isoform specific antibodies, we demonstrate that the increase in total PKC activity is mainly due to the PKC alpha isoform. PKC alpha protein expression increased up to 8 fold during in vivo aging. Collagenase (MMP-1) gene transcription and protein expression also increased with age, concomitant with the increase in protein kinase C alpha. Furthermore, alpha-tocopherol, which inhibits protein kinase C activity, is able to diminish collagenase gene transcription without altering the level of its natural inhibitor, tissue inhibitor of metalloproteinase, TIMP-1. We propose that an aging program leads to increased protein kinase C alpha expression and activity. This event would induce collagenase overexpression followed by increased collagen degradation. Our in vitro experiments with skin fibroblasts suggest that alpha-tocopherol may protect against skin aging by decreasing the level of collagenase expression, which is induced by environmental insults and by aging. (C) 1999 Elsevier Science Inc.
Keywords: collagenase; PKC; tocopherol; aging; fibroblasts; free radicals; HUMAN-SKIN FIBROBLASTS; MUSCLE CELL-PROLIFERATION; TRANS-RETINOIC ACID; GENE-EXPRESSION; REPLICATIVE SENESCENCE; TISSUE INHIBITOR; LIFE-SPAN; TRANSCRIPTIONAL REGULATION; INTERSTITIAL COLLAGENASE; ULTRAVIOLET-RADIATION